Sequence analysis of the beta-lactamase repressor from Staphylococcus aureus and hybridization studies with two beta-lactamase-producing isolates of Enterococcus faecalis. - Smith, M C (1992)
The putative beta-lactamase (Bla) repressor gene, blaI, from the staphylococcal plasmid pI524 was isolated, and the DNA sequence was determined. The sequence of blaI was found to be identical to the blaI sequence from pI9789 (blaI blaZ seg-1), a plasmid related to pI524. A blaI probe from pI524 was hybridized with plasmid and genomic DNA from Bla+ Enterococcus faecalis isolates HH22 and PA. The Bla structural gene of HH22 has been previously shown to be of staphylococcal origin, but DNA homologous to the staphylococcal Bla repressor was not found, indicating that the constitutive production of beta-lactamase in these E. faecalis isolates may be the result of a missing repressor protein.